2019
DOI: 10.1128/aem.02462-18
|View full text |Cite
|
Sign up to set email alerts
|

LysPBC2, a Novel Endolysin Harboring a Bacillus cereus Spore Binding Domain

Abstract: To control the spore-forming human pathogen Bacillus cereus, we isolated and characterized a novel endolysin, LysPBC2, from a newly isolated B. cereus phage, PBC2. Compared to the narrow host range of phage PBC2, LysPBC2 showed very broad lytic activity against all Bacillus, Listeria, and Clostridium species tested. In addition to a catalytic domain and a cell wall binding domain, LysPBC2 has a spore binding domain (SBD) partially overlapping its catalytic domain, which specifically binds to B. cereus spores b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(43 citation statements)
references
References 58 publications
(66 reference statements)
0
40
0
Order By: Relevance
“…Endolysins encoded by phages infecting the B. cereus group show differences regarding the targeted bacteria, ranging from a narrow to a broad activity spectrum. For instance, LysPBC5 is only able to lyse members of the B. cereus group whereas LysPBC2 is also active against other Bacillus spp., and even L. monocytogenes and Clostridium perfringens [11,33]. PlyB221 and PlyP32 both have intermediate activity spectra, as they are active against strains of the B. cereus group but also B. megaterium, B. pumilus, and B. licheniformis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Endolysins encoded by phages infecting the B. cereus group show differences regarding the targeted bacteria, ranging from a narrow to a broad activity spectrum. For instance, LysPBC5 is only able to lyse members of the B. cereus group whereas LysPBC2 is also active against other Bacillus spp., and even L. monocytogenes and Clostridium perfringens [11,33]. PlyB221 and PlyP32 both have intermediate activity spectra, as they are active against strains of the B. cereus group but also B. megaterium, B. pumilus, and B. licheniformis.…”
Section: Discussionmentioning
confidence: 99%
“…B. cereus sensu stricto (s.s), Bacillus thuringiensis, Bacillus anthracis, Bacillus weihenstephanensis, Bacillus mycoides, Bacillus pseudomycoides, and Bacillus cytotoxicus are the seven species most commonly recognized as members of this group, but other species have been suggested as new members [15,16]. In the last few years, several endolysins of phages infecting diverse B. cereus group members have been identified and characterized [11,[17][18][19][20][21]. Deep-Blue [22,23] and Deep-Purple [24], two phages infecting the B. cereus group, belong to the families Herelleviridae and Siphoviridae, respectively.…”
Section: Of 16mentioning
confidence: 99%
See 1 more Smart Citation
“…It is also possible that the already described P. larvae phages may encode previously unidentified lytic enzymes. It has been demonstrated that lysins may specifically bind spores, e.g., lysin LysPBC2 encoded by Bacillus cereus ( Kong et al, 2019 ). These findings suggest the probability of isolating an endolysin with activity against spores produced by Gram-positive bacteria similar to P. larvae .…”
Section: Phage Application Potentialmentioning
confidence: 99%
“…The modular structure of these enzymes creates the possibility of engineering proteins and constructing endolysins with new or improved properties. Enhanced lysin activity can be achieved by manipulating their functional domains, e.g., random or directed mutagenesis in the cell-binding domain ( São-José, 2018 ; Kong et al, 2019 ), shuffling and fusion of catalytic domains with cell-wall binding domains of different origin and properties to obtain chimeric enzymes (chimeolysins), fusion of full-length lytic enzymes, domain deletion, addition or duplication, fusion to peptides, and combination of these methods ( São-José, 2018 ). With respect to AFB sporicidal activity, it would be desirable for tailored enzymes that would penetrate the spore coat and then facilitate bond cleavage in peptidoglycan layers both in the core wall and spore cortex ( Todar, 2009 ).…”
Section: Phage Application Potentialmentioning
confidence: 99%